Microbial Diversity of Betula Trees: Pollen, Catkins, Leaves Relatively of Flowering - Tetiana V. Shevtsova (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2016)
Quantitative microbiological analysis by dilution plating method of pollen and additional male and female catkins, leaves of Betula verrucosa Ehrh. and its two cultivars: ‘Purpurea’ and ‘Youngii’ relatively of flowering period of Betula has been realized with the aim to provide new knowledge of the microbiological quality of anemophilous pollen for processing and its further application. Qualitative microbiological analysis with MALDI-TOF MS Biotyper was used in the identification of aerobic, anaerobic mesophilic bacteria and coliforms. Mixed microbiota was determined, consisting of aerobic (4.68–4.89 log cfu/g) and anaerobic (3.30–3.48 log cfu/g) mesophilic bacteria, lactobacilli (0–3.48 log cfu/g), coliform bacteria (0–4.57 log cfu/g), fungi and yeast (3.78–3.95 log cfu/g) on the pollen grains, that indicates acceptable quality in comparison with the microbiological quality parameters for bee pollen. Pantoea agglomerans was found associated with pollen of Betula verrucosa Ehrh. Recommendations on the collection of anemophilous pollen were established.